Analisis Perencanaan Tenaga Kerja Berbasis Industri 5.0 pada PT. Vidya Indonesia Prima Bandung - Miranti Asri Nur Sapitri; Resya Dwi Marselina; Pani Hermawan; Meysia Laudia; Razwa Andika Prasetya (Journal of Science, Technology, and Innovation, 2026)
The transition toward Industry 5.0 requires organizations to develop workforce planning approaches that emphasize not only technological utilization but also the enhancement of human resources as the core of the work ecosystem. This study aims to analyze workforce planning practices implemented by PT. Vidya Indonesia Prima Bandung and identify strategies that improve organizational performance effectiveness. A qualitative descriptive approach was employed through interviews, observations, and documentation, with data analyzed using reduction, display, and conclusion-drawing techniques supported by triangulation. The findings reveal that the company applies flexible workforce planning through competency development, open organizational communication, multitasking practices, and the utilization of digital technologies based on the principle of “Assist, Not Replace.” Industry 5.0-based workforce planning is implemented through digital literacy enhancement, talent management, and continuous upskilling and reskilling programs, which contribute to improved adaptability, productivity, and employee performance effectiveness.